Reproducing kernel functions for linear tenth-order boundary value problems - Akgul, Ali; Akgul, Esra Karatas; Orcan, Baris; İnç, Mustafa (E D P Sciences, 2018)
Higher order differential equations have always been an onerous problem to investigate for the mathematicians and engineers. Different numerical methods were applied to get numerical approximations of such problems. This paper gives some reproducing kernel functions to find approximate solutions of the tenth-order boundary value problems (BVPs). These reproducing kernel functions are very important in the reproducing kernel Hilbert space method.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Spline Solutions